(untitled) (MCIT: Proceedings of International scientific and practical conference, 2023)
The article describes radio beacon systems and presents a mathematical solution to determine the location of an unmanned aerial vehicle (UAV) equipped with a direction-finding device. This system ensures continuous flight and allows for determining the exact coordinates of targets, regardless of satellite signals. It facilitates the successful completion of combat missions in adverse weather conditions and when using radio electronic warfare (REW) systems based on signals received from radio beacons.